Persepsi Nasabah Pada Fitur Layanan Top Up E-Wallet BSI Mobile di Bank Syariah Indonesia Kantor Cabang Pembantu Kuta - Ika Aisyah; Raden Agrosamdhyo; Ely Mansur (Jurnal Nirta : Inovasi Multidisiplin, 2023)
The Top Up E-Wallet service feature is one of the service features available on BSI Mobile provided by Bank Syariah Indonesia for customers who often use cashless payment systems so that customers can easily top up their digital wallet balances. The purpose of this research is to find out how to use the BSI Mobile E-Wallet Top Up service feature at BSI KCP Kuta, find out the advantages of the BSI Mobile E-Wallet Top Up service feature, find out customer perceptions of the BSI Mobile E-Wallet Top Up service feature in BSI KCP Kuta. The research method used in this research is a descriptive qualitative method. Informants in this study were selected using random sampling techniques. For data collection techniques using observation, interviews and documentation methods. Data analysis techniques include data reduction, data presentation, drawing conclusions. Meanwhile, the validity of the data uses triangulation which can help researchers to test the validity of information from various sources. The research results found: How to use the BSI Mobile E-Wallet Top Up service feature is quite easy for BSI KCP Kuta customers to understand and use. The advantage of the BSI Mobile E-Wallet Top Up Service Feature is that customers can easily get access to information related to the service feature, the transactions that can be carried out by this service feature are varied, the innovation of this service feature is that there is a reminder to donate or give alms after the customer makes a Top Up transaction . Customer perception of the BSI Mobile E-Wallet Top Up service feature is quite good. Perception is interested in using this service feature because it is considered to have cheap admin costs and is easy to use. The perception target is considered to have a complete digital balance according to customer needs. It was found that there were bad network problems and server downs which made Top Up transactions fail.